Faktor yang Memengaruhi Strategi Koping Masyarakat yang Tinggal Berdampingan dengan Penderita Skizofrenia - Retno Lestari; Ah Yusuf; Rachmat Hargono; Febri Endra Budi Setyawan; Ahsan Ahsan (Media Kesehatan Masyarakat Indonesia, 2020)
The increasing number of patients with schizophrenia in the community requires positive support from all parties so that they can be more productive and independent. Stigma and discrimination that are still prevalent become the biggest obstacles to the community coping strategies in responding to the presence of patients with schizophrenia. This study aimed to analyze the factors that influence the coping strategies of people living side by side with patients with schizophrenia. This study used an analytic observational design with a cross-sectional approach. The population in this study was the people who live around patients with schizophrenia in the working area of Bantur Community Health Center, Malang Regency, East Java. There were 138 respondents selected based on the multi-stage random sampling technique. The predictor variables examined were problem appraisal (X1), social capital (X2), and social support (X3). Data were analyzed using logistic regression tests. The results of the study indicate that the fac-tor that influences community coping strategies is social capital (X2). The resulting regression equation is Y = 5.627 + 0.733X1 + 1.739X2 - 0.021X3. Therefore, it can be concluded that social capital is a predictor that in-fluences community coping strategies. It is therefore recommended that the community could strengthen their social capital to help the recovery of patients with schizophrenia.